2007
DOI: 10.1111/j.1365-294x.2007.03321.x
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of a rapidly evolving speciation phenotype in the Hawaiian cricket Laupala

Abstract: In mate recognition systems, the functional necessity to coordinate traits involved in sexual communication should result in reduced pairing potential for new variants outside the distribution of common reproductive signals. Yet, many closely related, sexual species differ in mate recognition traits, suggesting that directional selection influences the divergence of mate recognition systems. Species of the endemic Hawaiian cricket genus Laupala are morphologically and ecologically cryptic, although both male c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
126
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(144 citation statements)
references
References 58 publications
16
126
2
Order By: Relevance
“…Previously, the pulse rates of 190 F 2 males from this cross were reported (23) (Fig. 1C), showing a normal distribution between the pulse rates of the 2 parental species (F 2 pulse rate mean Ϯ SD ϭ 1.86 Ϯ 0.36; Shapiro-Wilk: W ϭ 0.994, P ϭ 0.636) (23). (23), equal to the number predicted by cytological analysis (24).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Previously, the pulse rates of 190 F 2 males from this cross were reported (23) (Fig. 1C), showing a normal distribution between the pulse rates of the 2 parental species (F 2 pulse rate mean Ϯ SD ϭ 1.86 Ϯ 0.36; Shapiro-Wilk: W ϭ 0.994, P ϭ 0.636) (23). (23), equal to the number predicted by cytological analysis (24).…”
Section: Resultssupporting
confidence: 52%
“…Male L. kohalensis and L. paranigra songs have pulse rates of 3.72 Ϯ 0.128 pulses per second (pps) and 0.71 Ϯ 0.079 pps, respectively ( Fig. 1 A) (23). Previously, the pulse rates of 190 F 2 males from this cross were reported (23) (Fig.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The strikingly rapid (and possibly sympatric) radiation among the Hawaiian Laupala crickets (Mendelson and Shaw, 2005) is probably driven by divergence in calling song and preference (Shaw and Parsons, 2002). By using a combination of QTL studies and investigations of segregation patterns in F2 hybrids between two closely related species of Laupala crickets Shaw et al (2007) found that many genes with small effects were involved in the determination of song and that there was no disproportionate large X effect. To summarize, based on theoretical expectations and on interspecific empirical studies (Table 1) there is more evidence suggesting a large Z effect than a large X effect in the divergence of sexual signalling systems.…”
Section: Speciation and Sex-linked Genesmentioning
confidence: 99%